Students' Perception on Their Positive Thinking in Learning English as a Foreign Language - Rusmiyadi, Rusmiyadi; Khatimah, Khusnul (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research explores the role of positive thinking in the context of learning English as a foreign language, focusing on students' perceptions of how their optimistic outlook influences their language learning experiences. Employing a mixed-methods approach, the study combines quantitative data from a survey administered to 100 undergraduate students at the University of Muhammadiyah Kalimantan Timur with qualitative insights from semi-structured interviews. The findings reveal that students generally exhibit high levels of positive thinking, which significantly impacts their motivation, reduces anxiety, increases class participation, fosters resilience, and enhances overall academic performance and satisfaction. Quantitative analysis shows strong positive correlations between positive thinking and various aspects of language learning, while qualitative data provide deeper insights into how positive thinking helps students set and achieve goals, build confidence, engage actively in class, overcome challenges, and enjoy the learning process. This study contributes to the existing literature by providing empirical evidence on the benefits of positive thinking in language learning. It underscores the importance of integrating positive psychology principles into language education to improve student outcomes. Practical implications for language educators include fostering a positive classroom environment, encouraging optimism and self-efficacy, promoting active engagement, and building students' resilience.